Impact of GLP-1 receptor agonist versus omega-3 fatty acids supplement on obesity-induced alterations of mitochondrial respiration - Jansen, Kirsten M.; Dahdah, Norma; Gama-Perez, Pau; Schots, Pauke C.; Larsen, Terje S.; Garcia-Roves, Pablo M. (Frontiers in Endocrinology, 2023)
The aim of this study was to compare administration of the glucagon-like peptide-1 (GLP-1) analogue, exenatide, versus dietary supplementation with the omega-3 fatty acid-rich Calanus oil on obesity-induced alterations in mitochondrial respiration. Six-week-old female C57BL/6JOlaHSD mice were given high fat diet (HFD, 45% energy from fat) for 12 weeks to induce obesity. Thereafter, they were divided in three groups where one received exenatide (10 µg/kg/day) via subcutaneously implanted mini-osmotic pumps, a second group received 2% Calanus oil as dietary supplement, while the third group received HFD without any treatment. Animals were sacrificed after 8 weeks of treatment and tissues (skeletal muscle, liver, and white adipose tissue) were collected for measurement of mitochondrial respiratory activity by high-resolution respirometry, using Oroboros Oxygraph-2k (Oroboros Instruments, Innsbruck, Austria) It was found that high-fat feeding led to a marked reduction of mitochondrial respiration in adipose tissue during all three states investigated - LEAK, OXPHOS and ETS. This response was to some extent attenuated by exenatide treatment, but not with Calanus oil treatment. High-fat feeding had no major effect on hepatic mitochondrial respiration, but exenatide treatment resulted in a significant increase in the various respiratory states in liver. Mitochondrial respiration in skeletal muscle was not significantly influenced by high-fat diet or any of the treatments. The precise evaluation of mitochondrial respiration considering absolute oxygen flux and rations to assess flux control efficiency avoided misinterpretation of the results. We conclude that exenatide increased hepatic mitochondrial respiration in high-fat fed mice, but no clear beneficial effect was observed in skeletal muscle or fat tissue. Calanus oil did not negatively affect respiratory activity in these tissues, which maintains its potential as a dietary supplement, due to its previously reported benefits on cardiac function.